On photography a philosophical inquiry - Costello, Diarmuid (Thinking in action, 2018)
What is photography? Is it a source of knowledge or an art? Many have said the former because it records the world automatically, others the later because it expresses human subjectivity. Can photography be both or must we choose? Written in a clear and engaging style, On Photography is essential reading for anyone interested in the philosophy of photography, aesthetics, art, and visual studies. -- Provided by publisher.